Hepatic Hydatid Cyst Mimicing Reflux Esophagitis in Pregnancy: A Case Report - Ahmet Cantuğ Çalışkan; Hakan Aytan; Fazlı Demirtürk (Medical Network, 2009)
Hydatid cyst in pregnancy is a rare pathology and its diagnosis and treatment is a complex problem.Cyst hydatid disease can be localized in every organ and frequently seen in Turkey.This report describes the clinical features,evolution and treatment of a pregnant women complaining with upper gastrointestinal symptoms. A 27-year-old multigravida was admitted to our hospital in her 21st week of pregnancy because of gastroesophageal reflux and dyspeptic complaints.A 7×5×6 cm hepatic hydatid cyst was diagnosed on sonographic examination. The diagnosis was confirmed by an indirect hemagglutination test. The patient refused all of the treatment options and we followed her untill the end of pregnancy. Cesarean section was performed because of her previous sections and we removed the hepatic cyst after delivery. Every physician should be aware of this potential problems because a hydatid cyst can enlarge and rupture during pregnancy and be fatal to both mother and baby.